If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 52 = 2x + 24 Reorder the terms: 52 + 6x = 2x + 24 Reorder the terms: 52 + 6x = 24 + 2x Solving 52 + 6x = 24 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 52 + 6x + -2x = 24 + 2x + -2x Combine like terms: 6x + -2x = 4x 52 + 4x = 24 + 2x + -2x Combine like terms: 2x + -2x = 0 52 + 4x = 24 + 0 52 + 4x = 24 Add '-52' to each side of the equation. 52 + -52 + 4x = 24 + -52 Combine like terms: 52 + -52 = 0 0 + 4x = 24 + -52 4x = 24 + -52 Combine like terms: 24 + -52 = -28 4x = -28 Divide each side by '4'. x = -7 Simplifying x = -7
| B-24.6=5 | | 4p-15=1 | | x/5-7=x+6/3 | | 3+12=9y+4-8y | | 16=x/11 | | 1/x+3/7=5/x | | 5(x+8)=0 | | 7x+3(2x)=39 | | 4(2x-1)-2(3x+5)=x+4 | | 2/3+x^2-5/6+x=0 | | 12+d+8+4d= | | 2/3x^2-5/6x=0 | | 2/3x^2-5/6x | | 5/11x5/12 | | 2(1+5x)=82 | | 24=4x-10 | | 10(r-6)/10r | | -b+2=-.5 | | 5+9x=1+3x | | 6x+3x+x= | | 12y+6-11y=14.5 | | 8x+2x=40 | | 10=4a+10 | | 5/3x=1/x+2 | | 9h-15=75 | | (4+2x)2=2+-2 | | 2x/3+x/2=7/4+x | | -b+2=.5 | | -4*0+8y=-32 | | 3t^2-180=0 | | 3x/4=8+x/2 | | n-9=(-14) |